Trabalho através das plataformas digitais: da liquefação da modernidade à hermenêutica constitucional da solidariedade e do valor social do trabalho - Leão, Demetrius Almeida (2023)
The contemporary symbiosis between Information and Communication Technologies (ICTs) and work has given rise to the formation of new labor dynamics, causing redesigns in the world of work and, consequently, of Labor Law itself and public policies focused on the topic. With this evidence, the phenomenon of work carried out through digital platforms can be identified as a so-called disruptive form, fragmenting work and, at the same time, creating new forms of direction and control over it. The question arises whether the forms presented in this platform capitalism call for the need for a new legal architecture capable of offering responses to the peculiarities of on-demand work through applications or whether, on the contrary, the legal system is capable of encompassing such types of work, in order to examine: What are the bases for building a concept of decent platform work? The contributions are relevant from the point of view of the economic analysis of the precariousness of work and the social impact of this same precariousness, also revealing how the constituted powers face the issue, regarding the protective structures of work and the application of these structures to the phenomenon. To face the problem, a hypothetical-deductive method is used and an innovative solution in legal interpretation is sought within the Law itself, with the objectives of preserving work values (based on the Constitution and the ILO) to protect platform workers, recognizing the liquidity of established socio-labor relations, which, used as a distortion of communicative action, impose the need for a new normative instrument that conditions the protection of workers based on the social value of work, constitutionally guaranteed. The aim, therefore, is to identify platformization as a mark of a light and floating capitalism (Bauman), marked by the weakening of ties and a form of precariousness and flexibility of work, which uses very sophisticated mechanisms of invisible powers embedded in the technologies present in the applications, in addition to the communicational distortion used by companies that aim to surreptitiously convert workers into entrepreneurs of themselves, in a pure economic rationality aimed at increasing surplus value and precariousness of the worker, who voluntarily subjects himself to the precarious process, losing classic forms of legal protection. The work carried out through platforms is received in different ways, according to the social, legal and economic environments with which it interacts, adapts and suffers resistance and countries react, within their structures, trying to align or impose minimum conditions by which the work carried out through platforms may (or may not) exist, in their systems, through regulations and through judicial activity. In this sense, the research proposes, after revealing the lack of disruption in structured work based on digital platforms, an innovative construction to recognize platform workers as employees, in a hermeneutic-constitutional option of recognizing the vulnerability of this worker, in the terms proposed in this text. , especially in an underdeveloped environment like Brazil – full application of constitutional labor rights to platform workers, pointing out the necessary interpretation aligned with a solidary rationality, based on the social value of work and human dignity and the prohibition imposed by the democratic principle on the exercise of invisible powers, typical of work relationships through platforms, a construction aimed at formulating a concept of decent platform work.